Discourse Study Of The Experiential Function In The Miss Universes Speeches 2019 - Sari, Nurleni Indah (Universitas Muhammadiyah Sumatera Utara, 2021)
The aim of study is to investigate the kinds of process of experiential function are used in the Miss Universes Speeches 2019, to elaborate the realization of the process of experiential function, and to reason for the used of process of experiential function in the Miss Universes Speeches 2019. This study used descriptive qualitative method in analyzing the data. The data was taken from Miss Universes Speeches 2019 script. The script consisted of 8 pages were taken as the data. From the data obtained, it was found that Material process, 66 times (37.71%), Relational process 62 times (36.57%), Mental process 36 times (20.57%), Verbal process 5 times (2.86%), Existential process 3 times (1.71%), and Behavioural process only one time (0.57%). In this research, material process is the most dominantly kinds process of experiential function used by utterances in the Miss Universes Speeches 2019.The kinds process of experiential function because its used for talking about their experiences, the policy in the future. The dominant kinds process of experiential function was material process as the way to persuade, to motivate and convey information or insight the audiences in the Miss Universes Speeches 2019.